Correlation between Malocclusion and Allergic Rhinitis in Pediatric Patients: A Systematic Review - Marco Farronato; Valentina Lanteri; Andrea Fama; Cinzia Maspero (MDPI AG, 2020)
Background: Oral breathing, nasal obstruction and airway space reduction are usually reported as associated to allergic rhinitis. They have been linked to altered facial patterns and dento-skeletal changes. However, no firm correlation based on the evidence has been established. This systematic review has been undertaken to evaluate the available evidence between malocclusion and allergic rhinitis in pediatric patients. Methods: The research refers to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines, databases (Medline, Cochrane Library, Pubmed, Embase and Google Scholar) were screened, the quality was evaluated through Quality Assessment of Diagnosfic Accuracy Studies (QUADAS-2). Results: The articles selected (6 out of initial 1782) were divided on the basis of the study design: two observational randomized study, three case-control study, one descriptive cross-sectional study, and one longitudinal study. A total of 2188 patients were considered. Different results were reported as related to allergic rhinitis ranging from a higher incidence of dental malocclusion, to an increase of palatal depth, and in posterior cross-bite about anterior open-bite and to longer faces and shorter maxillas. Conclusions: Most of the studies selected found a rise in the prevalence of both malocclusion and allergic rhinitis in children. However, the level of bias is high, impaired by a poor design and no conclusive evidence can be drawn.